ANALISIS FAKTOR PENGHAMBAT KURANGNYA MINAT MEMBACA DAN MENULIS PADA SISWA KELAS III DI SD SWASTA REFORMASI PLUS - Maria S. Dirgahayu; Angelina C. O. R . Lake; Konradus Silvester Jenahut; Rince S. M. Benu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the inhibiting factors that cause a lack of interest in reading and writing in grade III students at Reformasi Plus Private Elementary School. This study is a qualitative study with a descriptive approach. The subjects were grade III students, their homeroom teachers, and their parents. Data collection techniques used were observation, interviews, and documentation. The results of this study indicate that various factors may contribute to low interest in reading and writing among students. Internal factors, such as lack of learning motivation, limited initial understanding, or low self-confidence, can be among the obstacles. In addition, external factors such as lack of family support, a less conducive learning environment, or less engaging learning methods can also play a significant role. Based on these issues, teachers should be able to understand the difficulties experienced by students early on. This is done so that teachers have more accurate information to address and improve the learning system provided.